Presentation is loading. Please wait.

Presentation is loading. Please wait.

Solve by Substitution 2x + y = 7 3x + 3y = - 3.

Similar presentations


Presentation on theme: "Solve by Substitution 2x + y = 7 3x + 3y = - 3."— Presentation transcript:

1 Solve by Substitution 2x + y = 7 3x + 3y = - 3

2 Solve by Graphing Solution: (-1, 3)

3 Questions over HW?

4 Skills Check

5 Solve Systems of Equations by Elimination

6 Steps for Elimination:
Arrange the equations with like terms in columns Add the equations. Substitute the value to solve for the other variable. Check

7 EXAMPLE 1 (-1, 3)

8 EXAMPLE 2 4x + 3y = 16 2x – 3y = 8 (4, 0)

9 EXAMPLE 3 3x + 2y = 7 -3x + 4y = 5 (1, 2)

10 Classwork Solve (-2, 2) (-1, 4) (-1, 2)
Use elimination to solve each system of equations. 4. -6x – 5y = m + 4n = x + y = 1 6x – 7y = m + 2n = x – y = -3 (-1, 2) (-2, 2) (-1, 4)

11 Classwork (-1, 2) (1, 1) (-3, 4) Solve
Use elimination to solve each system of equations. 7. 2x + 3y = x + 3y = x – 2y = 4 -2x – 4y = x + 4y = x + 2y = 3 (-3, 4) (-1, 2) (1, 1)

12 Homework Practice Worksheet


Download ppt "Solve by Substitution 2x + y = 7 3x + 3y = - 3."

Similar presentations


Ads by Google